2016
DOI: 10.1371/journal.pone.0154469
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Normal Range of Serum Phosphorus on the Incidence of End-Stage Renal Disease by A Propensity Score Analysis

Abstract: BackgroundAlthough hyperphosphatemia is deemed a risk factor of the progression of chronic kidney disease (CKD), it remains unclear whether the normal range of serum phosphorus likewise deteriorates CKD. A propensity score analysis was applied to examine the causal effect of the normal range of serum phosphorus on the incidence of end-stage renal disease (ESRD).MethodsA retrospective CKD cohort of 803 participants in a single institution was analyzed. Propensity score was estimated using 22 baseline covariates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…The meta-analysis suggested that every 1 mg/dL increase in serum Pi was independently associated with an increased risk for kidney failure (HR 1.36; 95% CI 1.20–1.55) [37]. An increased phosphate load can result in tubular injury, interstitial fibrosis, endothelial dysfunction, and vascular calcification via the direct effect of either phosphate or calciprotein particles [38]. Such findings suggest that not only a decrease in serum indoxyl sulfate but also a decrease in serum Pi might contribute to ameliorate kidney function in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis suggested that every 1 mg/dL increase in serum Pi was independently associated with an increased risk for kidney failure (HR 1.36; 95% CI 1.20–1.55) [37]. An increased phosphate load can result in tubular injury, interstitial fibrosis, endothelial dysfunction, and vascular calcification via the direct effect of either phosphate or calciprotein particles [38]. Such findings suggest that not only a decrease in serum indoxyl sulfate but also a decrease in serum Pi might contribute to ameliorate kidney function in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, evidence shows that hyperphosphatemia in CKD is associated with poor renal prognoses. Moreover, a study of 803 CKD patients showed that higher serum phosphate levels were associated with an increased risk of ESRD, where the HR was about 17.6 at a time-averaged phosphorus level of 3.4 mg/dL, even in patients with normal serum phosphate levels [14].…”
Section: Discussionmentioning
confidence: 99%
“…Depend on studies the important risk factors for involving in ESRD are hyperphosphatemia, hypercalcemia, dyslipidemia, and hypoalbuminemia which impact on CVD morbidity directly. Especially, over normal range of P is a great risk factor of CKD patients [24,25]. Recent study indicated that 52.9% and 52% had hyperphosphatemia and hyperkalemia, respectively.…”
Section: Several Studies Have Shown An Association Between Increased mentioning
confidence: 99%